Changes of wound dimensions and pain assessment in response to hyperbaric oxygenation therapy - Mikołajewska, Emilia; Wawrzyniak, Sławomir; Dzięgielewski, Piotr; Goch, Aleksander (Journal of Medical Science, 2017)
Introduction. Novel approaches to wound healing can provide decreased risk of complications, wider possibilities of further treatment, rehabilitation and care, and improved patient’s quality of life. Most recent studies support the concept that HBOT accelerates the wound healing process. Aim. This paper aims at presentation and discussion the outcomes of a research on chronic wounds healing using the HBOT. Particular attention was paid to changes of wound dimensions and pain assessment in response to HBOT.Material and Methods. Inclusion criteria meet the medical records of eighty-nine adult patients with chronic wounds aged 18–85 years treated with HBOT. Wound length, wound width and pain were measured twice: before and after treatment.Results. There have been observed favourable and statistically significant changes in all measured areas: pain assessment, wound length, and wound width. Improvement of pain assessment occured in 94.38% of patients, improvement of maximal wound length occurred in 94.38% of patients, improvement of maximal wound width occurred in 86.52% of patients.Conclusions. Application HBOT in adult patients with chronic wound is an effective method of treatment. Age above 62 years, sex (men), lack of obesity, and number of HBOT sessions higher than 29 can be regarded as useful prognostic signs, however there is need for further research.
Keywords: rehabilitation; wounds healing; chronic wounds; hyperbaric oxygenation; hyperbaric oxygen therapy; HBOT